#TITLE_ALTERNATIVE# - EFFENDY (NIM 23005007), MOHAMMAD
The use of the reverse flow reactor (RFR) for tar conversion contained in producer gas is considered in this study. The operation of this RFR needs a particular attention, especially for choosing the operation parameter and reactor design due to the dynamic behavior of the fixed bed reactor. That is why the modeling and simulation of the RFR for tar conversion is indispensable in order to map the possible operating windows. The conversion of tar can be performed via steam reforming reaction to produce H2 and CO by the use of Ni/Al2O3 catalyst. The steam reforming of tar is an endotherming reaction, which requires heat. In this study, the energy consumption is provided by partial oxidation of H2 and CO using O2. The objective of this study is to investigate the dynamic behavior and the performance of the RFR for tar conversion. The focus of the study is to observe the ifluence of flow reversal on the tar conversion, product yield, and gas heating value. The scopes of research are literature study, modeling and simulation of RFR using a software package of FlexPDE version 3, and model validation for the case of RFR without reaction. The heat and mass transfer limitations are not included in this study. The validation in model without reaction shows good results and acceptable. Hence, this model can be developed further by involving the reaction of tar steam reforming tar. The regular reverse flow reactor results in a quasi-steady state regime when the switching time is larger than 900 s. In between 300-900 s, the reverse flow reactor shows a dynamic behavior, while when the switching time is less than 300 s, the reactor is in the sliding regime. During regular reverse flow operation, the conversion of tar is always lower than that of steady state, once-through operation. The tar conversion could span from 82,9% till 99,3%, correspoding to shifting operation regime from sliding-dynamic-quasi steady state. The gas heating values for regular flow reversal and steady state operation decrease, compared to the feed gas heating value. Compotition modulation combined with RFR may result in better gas heating value, but the conversion slightly decreases. The lowest tar conversion for the case of tH = ¼ ST is 62%. Varying feed position also lowers the tar conversion, but the gas heating value increases.